Needs Analysis on Robmanjar (Learning Partner Robot) Game Design to Stimulate Early Childhood Literacy - Sulistyawati Sulistyawati; Indri Astuti; Eny Enawaty (STKIP Singkawang, 2023)
The purpose of this study was to analyze the learning needs of early childhood by designing the Robmanjar (Learning Partner Robot) game to stimulate the development of basic literacy in children's SPNF SKB Pontianak City Playgroup. The design of the Robmanjar game was prepared based on an analysis of the needs of the children's learning outcomes in the Pontianak City SPNF SKB Play Group in the first quarter of the odd semester of the 2022/2023 school year. The research method used was survey research. The number of respondents consisted of 1 educator, 8 parents of students, and 8 children of the SPNF SKB Playgroup in Pontianak City. Data collection techniques used interviews, observation, and questionnaires. The data analysis technique used was descriptive quantitative and qualitative analysis. The results showed that the average results of the elements of achievement in learning the basics of literacy were still low because the level of achievement of children who developed as expected was still below 50%. The details of the developmental achievements of the elements of the basics of child literacy in the Pontianak City SPNF SKB Play Group were 40.6% of children who had not yet developed; 42.2% of children started to develop; 15.6% of children developed as expected; and 1.6% of children developed very well. For the learning achievement elements of basic literacy to increase, it is necessary to design types of games that can stimulate children's development in the learning achievement elements of basic literacy. The Robmanjar game is expected to stimulate aspects of child development in the Pontianak City SPNF SKB Playgroup in the learning achievement elements of basic literacy.